Difficulty-Usefulness Pyramid (DUP) as a Method of Selecting Priority Elements in the Use of Long-Term Contraceptive Methods - Sunarto Sunarto; Risky Ika Septiana Puspitasari; Myrna A. Mercado; Heru Santoso Wahito Nugroho; Suparji Suparji; Ayesha Hendriana Ngestiningrum (Humanistic Network for Science and Technology (HNST), 2022)
Family Planning is a program of the Indonesian government to regulate the rate of population growth by using contraceptive methods. Contraception is divided into two types, namely long-term contraceptive methods (MKJP) and non-long-term contraceptive methods (Non-MKJP). Factors that influence the use of contraception are fertile age couple knowledge about MKJP, costs, skills of officers, availability of tools, counseling-information and family planning education, husband's support, access to services, satisfaction with using contraceptives, and history of use. This research was conducted to determine what factors influence the selection of MKJP methods in Bulugunung Plaosan Village, Magetan Regency. The difference with other similar studies lies in the method, selection of influence factors used the Difficulty-Usefulness Pyramid (DUP) method. This study was a descriptive study involving 64 women of family planning Non-MKJP participants in Bulugunung Plaosan Village, Magetan Regency from January to May 2020. The data analysis used the calculation of the mean score of difficulty and usefulness for each element of the MKJP and calculated the range starting from the mean difficulty score up to the mean usefulness score. Focus group discussion method has been used to determinate of elements. The elements that were categorized as high priority were availability of family planning services, service fee of family planning, and communication, information and education of family planning. Keywords: elements; long-term contraception method; Difficulty-Usefulness Pyramid